SECURITY OF NATIONAL VITAL OBJECTS AND CERTAIN OBJECTIVES AGAINST THE FILLING OF ATMs BY THE POLICE IN PT. NAWAKARA ARTA KENCANA - Yudi Satrio Wibowo; Abdul Kadir (Universitas Muhammadiyah Tangerang, 2020)
The guarding of vital national objects and other objects towards the filling of ATM by the police at PT. Nawakara Arta Kencana is the title used by the writer. The main problem of this research is how the guarding mechanism of ATM money filing by the police and how the protection law of the guarding agent. This research used the Normative Empiris type, and the method of this research was descriptive qualitative. The source of primary data taken from an interview with the police and staff of PT. Nawakara Arta Kencana and from applicable laws. The result of this research showed that the guarding mechanism of ATM money filling belongs to PT. Nawakara Arta Kencana by the police was a request for guarding assistance in the form of cooperation agreement based on Regulation of the Chief of Police of the Republic of Indonesia number 13 of 2017 about defending service of vital objects and particular objects. The use of power in the implementation of policy actions according to the procedure of getting the protection and legal assistance based on Regulation of the Chief of Police of the Republic of Indonesia number 13 of 2017about the system for providing legal service by Kepolisian Negara Republik Indonesia.Keywords: Guarding, Vital Objects, and ATM fillingKeywords: Guarding, Vital Objects, and ATM filling